Molecular Identification of epsA and ompA genes for Acintobacter baumannii Isolated from Burn Wounds - Shaymaa Mohsin Shareef; Mohsan Hashim Risan (Indian Journal of Forensic Medicine & Toxicology, 2021)
This study was designed to molecular detection of epsA and ompA genes for Acinetobacter baumanniiIsolates that isolated from clinical. Burn wounds samples from a total of 80 clinical different Wounds,samples were collected from Ghazi Al Hariri Hospital and Baghdad hospital in Baghdad / Iraq. The resultsof the current study showed that seventy (87.5%) were clinical wounds positive samples, while the rest (10)were negative wounds samples (12.5 %). From 70 samples inoculated on the Chromagar Acinetobacter, 10isolate were grown on the medium, A. baumannii isolates on the Chromagar appeared as bright red coloniesafter 24h and incubation at 37 C . The results of epsA and ompA genes detection clarify that 8 isolate(80%) of A. baumannii isolates gave a positive result and carrying epsA and ompA genes while 2 (20%) ofAcintobacter baumannii isolates were lack the gene and no cross reactivity could be observed with any ofthe AS-3 and AS-9 isolates. The identification of A. baumannii isolates were depended on culturing theseisolates on CHROM agar Acinetobacter, MacConkey, blood, nutrient agar, biochemical tests and API NE 20test VITEK 2 . Compact were carried out the confirms. Results showed the amplification of epsA and ompAgenes for eight. A. baumannii isolates were AS-1, AS-2, AS-4, AS-5, AS-6, AS-7, AS-8 and AS-10. PCRproduct 531 bp of ompA gene and 451 bp of epsA gene.